The Association between Processed Meat Intake and the Prevalence of Type 2 Diabetes in Thais: a Cross-Sectional Study from the Electricity Generating Authority of Thailand - Thananya Ruengurairoek (2022)
Background: Type 2 diabetes (T2D) is a major health problem worldwide of which the complications are crushing burden. Previous studies reveal that consumption of processed meat is associated with higher incidence of T2D. However, the data outcomes are varied and the pathogenesis is still inconclusive. Objective: This study aims to assess the association between processed meat consumption and T2D, and to investigate the influence of health-related factors and processed meat consumption and T2D. Methods: A cross-sectional study was conducted in 2,017 subjects from population-based cohort study: the Electricity Generating Authority of Thailand study (EGAT) in 2013. Univariate and multivariate analysis were performed by logistic regression to reveal the association between processed meat intake and T2D and to adjust the potential confounders. The interaction terms were tested among these factors and T2D. Results: The amount of processed meat consumption had a negative trend on T2D (P for trend = 0.03). The associations with T2D were also found in male (OR = 2.07; P < 0.001), high waist circumference (WC) (OR = 2.58; P < 0.001), undergraduated level (OR = 1.40; P = 0.01) and low serum non-HDL cholesterol (OR = 2.99; P < 0.001). Conclusions: The higher processed meat intake has trend to increase a prevalence of T2D in all groups of BMI, WC, education level, serum cholesterol levels, smoking status and alcohol intake. Further long-term cohort study is warranted to confirm this finding.